Status, Management, and Governance of the Communal Grasslands of Ethiopia's Highlands: A Disappearing Asset for Mixed Crop-Livestock Livelihood Systems - Eba, Bedasa; Flintan, Fiona E.; Getachew, Tesfa; Sircely, Jason A. (International Livestock Research Institute, 2021)
There is little documentation about the status, management, and governance of the communal grasslands of Ethiopia's highlands. However, research being carried out by ILRI (International Livestock Research Institute) in northern Shewa, Amhara region, is highlighting their importance as a critical resource for those farmers engaged in mixed crop-livestock livelihood systems across the highland areas. These grassland areas range from 2 to 200 hectares and can be used by up to four different villages or kebele' and providing on average 10-20% of livestock feed for local farmers. However, this important resource is rapidly disappearing with encroachment of farming and tree-planting with species such as Eucalyptus spp. that kill grasses. The remaining grassland is often degraded through poorly organized grazing and overuse. In the past these communal areas made up around 50% of village areas, but this has now significantly reduced. Most of these communal grasslands have effectively no management and governance system, and rather are open access for all the local population with livestock to use. This situation results in almost no resting of pastures from grazing. Unlike individual lands in the area, landholding certificates are not provided for these highland communal grazing lands. Though in other parts of the country including in Amhara region, some of these lands have been registered to community user groups, this is not the case in most of northern Shewa. These findings show the need to improve the management/governance of these important communal resources with available opportunities through engagement and participation of the communities and stakeholders. Finally monitoring systems would be useful to detect changes in the communal grasslands condition, whether management adjustments should be made, and to provide recommendations for communities throughout the highlands on practical and effective grazing management strategies.